The genes associated with the development of cardiovascular diseases (Experimental biology, 2016)
Сandidate genes associated with the development of cardiovascular diseases such as atherosclerosis, hypertension, myocardial infarction, coronary heart disease, metabolic syndrome are searched. A created database of the genes, associated with the development of these diseases have been analyzed in a comparative aspect.  It has been shown that some of the genes involved in the development of all the forms of cardiovascular disease (AGTR1, ALDH2, APOE, ICAM1, IGF1, LPL, MTHFR, PON1, SERPINE1, TGFB1, VEGFA). It was also shown that there are genes are involved in the development of only some one form of cardiovascular disease (ACSL1, ADTRP, AKT1, ALMS1, ANXA5, AQP2, AR, ATP2B1, CASZ1, CDH13, CELSR2, CFTR, CTSL, CUL7, DAP, DYRK1B, FIGN, FN1, FOS, FTO, GSN, HDAC9, ICOS, INPPL1, JAK2, LPIN1, MKKS, EDD4L, NFE2L2, PRL, SMTN, SOCS1, SOCS3, UMOD, WNT5A).  These results provide the basis for identifying genes, whose expression is dependent on the action of microRNA, since research on the identification of associations of these candidate genes like miRNA targets are of great importance because the low molecular weight RNA selectively regulate the expression of all human genes and may cause the disease, and used in the treatment, diagnostics of these diseases. Cardiovascular disease - is the leading cause of death not only in Kazakhstan, but also throughout the world. Among the most common diseases, such as hypertension, metabolic syndrome, atherosclerosis, myocardial infarction, coronary heart disease. The problem of cardiovascular disease is one of the leading places among the major health problems of the XXI century, as it is one of the major causes of death, as well as temporary and permanent loss of working capacity of the population in the developed world.  Causes (etiology) occurrence of cardiovascular disease interconnected. Cardiovascular disease is multifactorial and arise under the influence of external and genetic factors. Currently, a huge amount of experimental work devoted to the search for  genetic factors (candidate genes), leading to the development of cardiovascular disease.  In the database NCBI (http://www.ncbi.nlm.nih.gov/) was searched gene, wherein the disease name as a keyword has been used. The audit was conducted by searching the relation of  this gene with the corresponding disease in publications over the past twenty years (http://www.ncbi.nlm.nih.gov/pubmed/). Thus, it appears link of gene with appropriate diseases, and created database of genes involved in the development of cardiovascular disease. Genes, associated with ischemic heart disease (174 genes), myocardial infarction (185 genes), atherosclerosis (213 genes),  hypertension (128 genes) and metabolic syndrome (182 genes) were found. A created database of the genes, associated with the development of these diseases have been analyzed in a comparative aspect.  It has been shown that some of the genes involved in the development of all the forms of cardiovascular disease (AGTR1, ALDH2, APOE, ICAM1, IGF1, LPL, MTHFR, PON1, SERPINE1, TGFB1, VEGFA). It was also shown that there are genes are involved in the development of only some one form of cardiovascular disease (ACSL1, ADTRP, AKT1, ALMS1, ANXA5, AQP2, AR, ATP2B1, CASZ1, CDH13, CELSR2, CFTR, CTSL, CUL7, DAP, DYRK1B, FIGN, FN1, FOS, FTO, GSN, HDAC9, ICOS, INPPL1, JAK2, LPIN1, MKKS, EDD4L, NFE2L2, PRL, SMTN, SOCS1, SOCS3, UMOD, WNT5A).  For example, revealed that more than 10 genes involved in the development of metabolic syndrome only. These results provide the basis for identifying genes, whose expression is dependent on the action of microRNA, since research on the identification of associations of these candidate genes like miRNA targets are of great importance because the low molecular weight RNA selectively regulate the expression of all human genes and may cause the disease, and used in the treatment, diagnostics of these diseases.
Keywords: atherosclerosis; hypertension; myocardial infarction; coronary heart disease; metabolic syndrome; gene; diagnosis.